BUILDING PURCHASE INTENTION: COMPANY IMAGE, PRODUCT KNOWLEDGE AND PRICE PERCEPTION - Ricardo, Ricardo (Dinasti Publisher, 2021)
The Literature Review Article Building Purchase Intention: Company Image, Product Knowledge and Price Perception is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literture Review article is using the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this study are: 1) Company Image is related to Purchase Intention; 2) Product Knowledge related to Purchase Intention; and 3) Price Perception related to Purchase Intention. Apart from these 3 exogenous variables that affect the endogenous variable of Purchase Intention, there are still many other factors including the variables of Place, Service Quality and Product Quality.